Relationship between body mass, peak power, and power-to-body mass ratio on sprint velocity and momentum in high-school football players - Jalilvand, F.; Banoocy, N. K.; Rumpf, M. C.; Lockie, R. G. (The Journal of Strength and Conditioning Research, 2019)
The ability to rapidly shift one's body mass horizontally or vertically is common within American football irrespective of field position, and the capacity to generate power is a favorable physical quality. This requires analysis in high-school football players, especially considering the body mass disparities that exist in this population. Sixteen high-school players (7 backs and 9 linemen) completed the vertical jump (VJ) to determine jump height, peak anaerobic power measured in watts (PAPw), and power-to-body mass ratio (P:BM), and a 36.58-m sprint (0-4.57, 0-9.14, and 0-36.58-m intervals) to determine sprint velocity and momentum. Independent-samples t-tests (p < 0.05) determined differences in these variables between the backs and linemen. Pearson's correlations (r; p < 0.05) computed relationships between body mass, VJ height, PAPw, P:BM, with 36.58-m sprint velocity and momentum on the pooled data. Linemen were heavier, and slower in the 36.58-m sprint, but had greater PAPw and sprint momentum compared with backs. Body mass exhibited negative relationships to velocity across all sprint intervals (r = -0.55 to 0.70), and positive relationships with momentum across all intervals (r = 0.95-0.96). The VJ correlated with sprint velocity across all intervals (r = 0.51-0.83), but not momentum. PAPw was positively correlated with body mass and momentum across all intervals (r = 0.77-0.85), but not velocity. There were significant correlations between P:BM with velocity (r = 0.51-0.85) and momentum (r = -0.53-0.62) across all intervals. Heavier high-school players could focus on improving P:BM to positively influence jumping ability and sprint velocity.